Synthesis of substituted quinolines via B(C6F5)3‐catalyzed aniline‐aldehyde‐pyruvate oxidative annulation. (30th October 2019) - Ling, Fei; Chen, Jiachen; Xie, Zhen; Hou, Huacui; Pan, Zhentao; Feng, Cong; Shen, Haiwei; Zhong, Weihui
Abstract: A metal‐free method to construct quinoline derivatives via B(C6 F5 )3 ‐catalyzed cyclization of anilines with aldehyde derivatives and pyruvates is described. This three‐component cascade reaction provides an efficient approach for the easy access to various substituted quinoline‐4‐carboxylic esters with 71% to 92% yield. The utility of this methodology was further demonstrated by gram‐scale formal synthesis of the antimalarial drug DDD107498. Abstract :